PHENOLIC COMPARISON BETWEEN COLOMBIAN RED WINES AND THOSE IMPORTED - DURÁN O., Daniel S.; TRUJILLO N., Yanine Y. (Vitae, 2009)
The phenolic compounds play an important role in the quality of red wines. They give sensorial characteristics like flavor, aroma, color, astringency, among others. In this study seven (7) red wines on the market were analyzed from different geographic origins of which the total index of polyphenols (IPT) was to be determined; also, to determine the quantity of tanines, quantity of Anthocyans and the chromatic characteristic. In the IPT analysis among all the wines a similar effect was produced without considering origin. The Colombian wines presented low values in the content of tanines and anthocyans lower than in the international wines. While all the wines present a medium value of color intensity of the chromatic characteristic, the Colombian wines showed less value. In so far as tone is concerned, the Colombian wines are similar to the international ones. According to the obtained results it is possible to be concluded that the IPT in all the wines is similar and that they are in the normal rank of a young red wine. Also it happens the same to the chromatic characteristics. Whereas the content of tanines and anthocyans Colombian wines they are lower than in the mattered.